Natural honey reduced atherogenic and coronary risk indices in Wistar rats - Olukanni, Olumide David; Alagbe, Yewande O.; Akande, Oreoluwa T; Olukanni, Adedayo T.; Daramola, Gbenga G.; Adeyemi, Oluyomi S. (Faculty of Medicine, Trisakti University, 2020)
BACKGROUNDThe biochemical mechanism underlying the nutraceutical effects of honey is poorly understood, thus making its functions more a matter of speculations. In this study, we investigated the effects of honey on the atherogenic and coronary risk indices in Wistar rats.METHODSAn experimental design comprising two groups of rats fed with normal rat chow but with the experimental group receiving 10% honey in water and the control group water alone, for five weeks. Blood samples were collected weekly from each group, and the level of superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH) and total protein were determined. The lipids profile (total cholesterol, total triglycerides, LDL and HDL) were also determined, and the atherogenic and coronary indices were estimated. Data were analyzed, and p<0.05 was considered significant.RESULTSThere were no significant changes in both groups’ serum SOD and CAT across the weeks of study. The LDL cholesterol of the honey-treated rats, however, decreased significantly (9.95 mg/dL) compared to the controls (27.07 mg/dL) (p=0.000). In contrast, honey intake elevated the HDL cholesterol (18.37 mg/dL) relative to 12.25 mg/dL in the control group (p=0.003). Consequently, honey treatment caused significant depletion of atherogenic and coronary risk indices (76.13%, p=0.001) and (50.37%, p=0.023) respectively. CONCLUSIONWe show evidence that the regular intake of honey, at a concentration as low as ten percent of total water intake, may lower factors for the onset of hypertension and coronary diseases.